Study on ice resistance of Antarctic krill ship with trawl under floating ice sea conditions - Xiong, Zhixin; Wu, Xinyuan; Guo, Yu; Fu, Zheng (Frontiers in Marine Science, 2024)
This study focused on a Chinese Antarctic krill vessel utilising continuous pumping fishing technology. The resistance characteristics of Antarctic krill ships trawling in floating ice areas is of great significance for the navigation and fishing of krill ships in ice areas. Firstly, MATLAB programming using discrete elements combined with genetic algorithms was used to construct a normal distribution ice flow model. Secondly, a fluid-structure coupling interface is created through the contact between the fluid and the trawl grid, and the displacement and resistance of the trawl grid are evaluated on the shared interface. Finally, the effects of ice density and ship sailing speed on ice resistance were studied. The results of the calculations results show that ice resistance is positively related to the concentration and speed of floating ice, moreover, there is a special speed point where ice resistance increases rapidly. As the speed increases, the proportion of trawl resistance to the total resistance continues to increase, while the proportion of ice resistance continues to decrease. This paper provides a reference for the navigation and fishing resistance assessment of Antarctic krill ships in floating ice areas.